Novel Insight Into the Role of ACSL1 Gene in Milk Production Traits in Buffalo - Lin, Yuxin; Sun, Hui; Shaukat, Aftab; Deng, Tingxian; Abdel-Shafy, Hamdy; Che, Zhaoxuan; Zhou, Yang; Hu, Changmin; Li, Huazhao; Wu, Qipeng; Yang, Liguo; Hua, Guohua (Frontiers in Genetics, 2022)
Understanding the genetic mechanisms underlying milk production traits contribute to improving the production potential of dairy animals. Long-chain acyl-CoA synthetase 1 (ACSL1) plays a key role in fatty acid metabolism and was highly expressed in the lactating mammary gland epithelial cells (MGECs). The objectives of the present study were to detect the polymorphisms within ACSL1 in Mediterranean buffalo, the genetic effects of these mutations on milk production traits, and understand the gene regulatory effects on MGECs. A total of twelve SNPs were identified by sequencing, including nine SNPs in the intronic region and three in the exonic region. Association analysis showed that nine SNPs were associated with one or more traits. Two haplotype blocks were identified, and among these haplotypes, the individuals carrying the H2H2 haplotype in block 1 and H5H1 in block 2 were superior to those of other haplotypes in milk production traits. Immunohistological staining of ACSL1 in buffalo mammary gland tissue indicated its expression and localization in MGECs. Knockdown of ACSL1 inhibited cell growth, diminished MGEC lipid synthesis and triglyceride secretion, and downregulated CCND1, PPARγ, and FABP3 expression. The overexpression of ACSL1 promoted cell growth, enhanced the triglyceride secretion, and upregulated CCND1, PPARγ, SREBP1, and FABP3. ACSL1 was also involved in milk protein regulation as indicated by the decreased or increased β-casein concentration and CSN3 expression in the knockdown or overexpression group, respectively. In summary, our present study depicted that ACSL1 mutations were associated with buffalo milk production performance. This may be related to its positive regulation roles on MGEC growth, milk fat, and milk protein synthesis. The current study showed the potential of the ACSL1 gene as a candidate for milk production traits and provides a new understanding of the physiological mechanisms underlying milk production regulation.